(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Highly active anti-retroviral therapy (HAART) is currently the main stay in the treatment of Human Immunodeficiency Virus (HIV) disease. This treatment regimen typically combines three or more antiretroviral drugs and like most drug combinations or polypharmacy, has side effects including those on reproductive function which could place HIV patients on HAART under double risk in terms of reproductive function. Part of tissue damage following HAART administration is blamed on oxidative stress. We therefore sought to explore effects of Omega 3 and Selenium, two common antioxidants on HAART-induced male reproductive impairment in a non-HIV animal model. Sixteen male adult Wistar rats weighing 120g to 250g used for the study were grouped into 4 groups of four rats each (control, HAART-only, HAART + Omega 3 and HAART + Selenium groups). Duration of daily administration was six weeks. Results showed no significant changes in pH of epidydimal semen among the groups. Sperm count and viability were significantly reduced in HAART-only compared with control (p<0.05) but increased in HAART + Omega 3 and HAART + Selenium groups compared with HAART-only group (p< 0.05). Sperm motility was significantly reduced in HAART-only compared with control group (p< 0.05). A significantly higher percentage of total sperm defects was observed in HAART-only group compared with control (p <0.05) but significantly lower in the HAART + Selenium compared with HAART-only groups (p<0.05). Serum testosterone was significantly reduced in HAART-only compared with control groups (p<0.05) but significantly increased in HAART + Omega 3 and HAART + Selenium groups compared with HAART- only group (p<0.05). Serum concentration of luteinizing and follicle stimulating hormones were not significantly different among the groups. Testicular concentration of malondialdehyde was significantly increased in HAART-only compared with control (p<0.05) but significantly reduced in HAART + Omega 3 and HAART + Selenium groups compared with HAART-only group (p<0.05 in each). Testicular glutathione peroxidase activity was significantly reduced in HAART-only and HAART + Selenium groups compared with control (p< 0.05), but significantly higher in HAART + Omega 3 and HAART + Selenium compared with HAART-only groups (p<0.05 each). Testicular superoxide dismutase activity was significantly lower in the HAART-only and HAART + Selenium compared with control (p<0.05) but significantly higher in HAART + Omega 3 and HAART + Selenium compared with HAART-only groups (p<0.05 each). Level of tumour necrosis factor – alpha in testes was significantly higher in HAART-only (p<0.05) but lower in the HAART + Selenium (p<0.05) groups compared with control. Tumor necrosis factor–alpha was however significantly reduced in HAART + Omega 3 and HAART + Selenium groups compared with HAART-only (p<0.05 each) groups. Interleukin-6 levels were significantly increased in all HAART-administered groups compared with control (p<0.05 each) though significantly reduced in HAART + Omega 3 and HAART + Selenium compared with HAART-only groups (p<0.05 each). In conclusion, co-administration of Omega 3 or Selenium with HAART ameliorates HAART-induced male reproductive impairment, alteration in redox and inflammatory status in rats. Keywords: HAART, male reproductive impairment, Omega 3, Selenium